Semantic shifts of pejorative terms on Instagram: A study of university students' online language - Rahmi Fhonna; Cut Lala Khatun Qalqasyandi (EduLite: Journal of English Education, Literature and Culture, 2026)
Language meaning is dynamic and often changes according to social and cultural contexts, particularly in digital communication. This study investigates the semantic shifts of pejorative terms used by university students on Instagram. It aims to identify frequently used pejorative terms and analyze how their meanings have shifted within online interactions. Employing a qualitative descriptive design with purposive sampling, the study involved ten students from the English Education Department (PBI) who actively use Instagram. Data were collected through observation of Instagram captions and comments, screenshots of relevant posts, and semi-structured interviews. The analysis was guided by semantic change theory, particularly the concept of pejoration, and applied a thematic coding procedure to identify semantic shifts based on contextual usage. The findings reveal ten commonly used pejorative terms, namely red flag, ghosting, cringe, toxic, Karen, dry text, trust issue, salty, pick me, and roasting. The analysis indicates that these expressions have undergone semantic shifts, with their meanings extending beyond their original lexical senses to convey negative social evaluations, interpersonal judgments, and identity positioning in online discourse. The findings further demonstrate that digital communication accelerates semantic change by enabling online communities to reshape lexical meanings through repeated contextual use. This study contributes to the understanding of semantic change in digital communication and provides implications for sociolinguistics, semantics instruction, and digital literacy education by highlighting the importance of context-sensitive language use in social media environments.